2004
DOI: 10.1007/s00441-004-1017-0
|View full text |Cite
|
Sign up to set email alerts
|

Tight junction protein MAGI-1 is up-regulated by transfection with connexin 32 in an immortalized mouse hepatic cell line: cDNA microarray analysis

Abstract: Gap junctions are considered to play a crucial role in differentiation of epithelial cells, including hepatocytes. Recently, we found that Cx32 but not Cx26 was closely related to tight junctional proteins in primary cultured rat hepatocytes (Kojima et al., Exp Cell Res 263:193-201, 2001) and that Cx32 formation and/or Cx32-mediated intercellular communication could induce expression and function of tight junctions in a mouse hepatic cell line (Kojima et al., Exp Cell Res 276:40-51, 2002). In this study, to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…In contrast, the membrane-bound form of MAGI-1 has been implicated in the control of TJs (34), which are lost in HPVpositive cells (25,35,43). The results reported here show that this loss is indeed a result of E6 directing the degradation of MAGI-1.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…In contrast, the membrane-bound form of MAGI-1 has been implicated in the control of TJs (34), which are lost in HPVpositive cells (25,35,43). The results reported here show that this loss is indeed a result of E6 directing the degradation of MAGI-1.…”
Section: Discussionmentioning
confidence: 48%
“…Although there is no information on the potential role of MAGI-1 in the nucleus, previous studies have implicated the membrane-bound form of MAGI-1 in the establishment of cellular TJs (34). It has also been shown that TJs are disrupted in HPV-positive cells, and a possible role for hScrib in this phenotype has been suggested (35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAR3 is part of the PAR complex which localizes and controls the maturation of TJs, and PAR3 is one of the prime regulators of TJ formation. Thus, the fact that MAGI-1 enhances PAR3 junctional localization strongly suggests the involvement of MAGI-1 in the establishment of cell polarity by inducing the formation of apical junctional structures (56). These results demonstrate that the loss of TJs in HPV-18-positive HeLa cells is a direct consequence of the ability of E6 to direct the degradation of MAGI-1 and might provide an explanation as to why this protein is targeted by the virus during the life cycle and malignant progression.…”
Section: Discussionmentioning
confidence: 95%
“…Several MAGI-1 binding partners have been found. For example, β-catenin and actin-binding proteins act as binding partners of MAGI-1 [15,16]. In epithelia, MAGI-1 is localized at tight junctions [16].…”
Section: Magis Involved In Cancer Developmentmentioning
confidence: 99%